Pengaruh Motivasi Kerja dan Disiplin Kerja terhadap Kinerja Pegawai - Heriyanto Heriyanto; Siti Noor Hidayati (Jurnal Maksipreneur, 2016)
Performance is the work result of the employees to achieve of some company goals.The purpose of this researches is to determine the effect of work motivation and work discipline the performance as partial and simultaneous at the BMD Institute. The population in this research a total of 70 employees that is also a sample of all the population in that office. Research using multiple regression analysis. The result showed work motivation and work discipline a significant positive effect on employee performance. It was also concluded that work discipline variable dominanly influenced on employee performance compared to work motivation.